Transcriptome insights into newcastle disease virus-mediated eradication of cholangiocarcinoma cells - Suphannee Thanyaphoo; Chanachai Sae-Lee; Wilasinee Thaopech; Warisa Amornrit; Mutita Junking; Pa-thai Yenchitsomanus; Naravat Poungvarin (PLoS ONE, 2025)
Newcastle Disease Virus (NDV) has emerged as a promising oncolytic viral therapy for various human cancers; however, its effectiveness against cholangiocarcinoma (CCA) remains unexplored. This study presents the capability of the lentogenic LaSota strain of NDV to eliminate two CCA cell lines, KKU-055 and KKU-100, as well as the potential molecular mechanisms underlying this effect. Comprehensive transcriptome analysis revealed alterations in gene expression within several pathways in CCA cells following exposure to the LaSota strain NDV, including those involved in TNF-alpha signaling via NF-kB, interferon alpha response, apoptosis, and IL-6/JAK/STAT3 signaling pathways. We remarkably observed a contrasting alteration in the expression of CXCR4, GRAMD1B, IGFBP4, and TGM2 genes in KKU-055 and KKU-100 cells. In addition, gene network analysis highlighted CCNA2, CDK1, DDX58, DHX58, EXO1, GBP1, IFIH1, IFIT1, IFIT2, IFIT3, IRF7, ISIG15, MX1, OAS1, OAS2, PARP9, TOP2A and XAF1 as potential hub genes influencing the response of CCA cells to NDV LaSota strain. Our findings offer evidence supporting the promise of NDV-based therapies as potential strategies for eliminating CCA cells.